Analyzing the Practice of Life Cycle Assessment. (20th May 2013) - Saunders, Christi L.; Landis, Amy E.; Mecca, Laurel P.; Jones, Alex K.; Schaefer, Laura A.; Bilec, Melissa M.
Summary Life cycle assessment (LCA) is a quantitative tool used to evaluate the environmental impacts of products or processes. With respect to buildings, LCA can be used to evaluate the environmental impacts of an entire building's life cycle. Currently LCA in the building area is used in a limited capacity, primarily to select building products. In order to determine the causality for the lack of whole‐building LCAs, focus groups with members of the architecture, engineering, and construction (AEC) communities were held. This article investigates the current level of knowledge of LCA in the AEC community and then discusses the benefits and barriers to the practice of LCA. In summary, the goal of the research was to identify why LCA is not used to its fullest potential in a whole‐building LCA. In an open forum and moderated setting, focus group participants were asked individually to self‐identify their experience with LCA, a brief education session on LCA was held, and then benefits and barriers to LCA were discussed. The focus group sessions were transcribed and systematically coded by social researchers in order to analyze the results. Hybrid flow and radar charts were developed. From the focus group results, the most important benefit to LCA was "provides information about environmental impacts." The results did not identify a prominent barrier; however, building‐related metrics were ascertained to be one of the more crucial barriers. The benefits and barriers classified by this analysis will be utilized to develop a subsequent online survey to further understand the LCA and AEC community.